Correlation between reactive oxygen species and oral conditions in elderly individuals with hypertension: a preliminary study - Nanan Nur'aeny; Wahyu Hidayat; Indah Suasani Wahyuni (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: The increased number of elderly people in Indonesia can be a positive phenomenon if their health is well-preserved. The elderly are influenced by physiological changes, environmental factors, and personal habits making them susceptible to chronic diseases. The oral cavity is also subject to change, one of the causes being reduced salivary flow that is manifested in dental caries and other oral health concerns. This disease is stimulated by oxidative stress in the body due to an imbalance between reactive oxygen species (ROS) and the antioxidant defense system. Purpose: This preliminary study aimed to investigate ROS-related hypertension and the state of oral health of elderly patients. Methods: The study constitutes a combination of cross-sectional observation and consecutive sampling. Twelve subjects, selected on the basis of inclusive and exclusive criteria, consisted of two males and ten females. Physical examinations and blood sampling were performed on all subjects. R version 3.4.1 for Windows operating system was used to perform statistical tests. Results: The 12 patients shared a history of hypertension, the lowest ROS level was 0.87 IU/ml, while the highest was one of 7.20 IU/ml. The correlation between ROS and oral conditions showed only ROS and tooth loss as having a significant positive correlation. An independent t test showed there to be a mean difference between ROS with Miyazaki index 1 and 2 but it was statistically insignificant. Conclusion: There was no correlation between the ROS level in the bloodstream and general oral health, except in the relationship between the ROS level in the bloodstream and tooth loss which had a positive correlation.